The Supply Chain Performance Measurement and Determination of Improvement Priorities Using the Supply Chain Operations Reference –Digital Standard (SCOR DS) and Analytic Network Process (ANP) Methods: (Case Study: Waste Management at Sendangsari) - Khairunnisa Naziro; Rahadian Perdana, Yandra (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2025)
Effective and efficient waste management remains a key challenge in supporting environmental sustainability at the regional level. This study was conducted at the Sendangsari Integrated Waste Management Site (TPST), located in Sleman, Yogyakarta. The aim of the research is to measure the performance of the waste processing supply chain and to determine the priority areas for improvement. The method used is the Supply Chain Operations Reference – Digital Standard (SCOR DS) approach to identify and categorize performance indicators based on six core processes: Plan, Order, Source, Transform, Fulfill, and Return. The Analytic Network Process (ANP) method is employed to assign weights to 18 Key Performance Indicators (KPIs) based on their level of influence and interrelation. These weights are then applied using the Objective Matrix (OMAX) method to calculate the performance scores for each indicator, which are subsequently classified using the Traffic Light System (TLS). The results show that TPST Sendangsari achieved an overall performance score of 7, with 9 KPIs falling in the green category, 7 in yellow, and 2 in red. These findings indicate that TPST Sendangsari requires further evaluation and improvement efforts, particularly for KPIs in the red and yellow categories, to enhance its overall performance.